Perinatal computerized patient record and archiving systems: pitfalls and enhancements for implementing a successful computerized medical record. - Kelly CS (Journal of Perinatal & Neonatal Nursing, 1999)
Interest in purchasing and installing a perinatal computerized patient record (CPR) and archiving system is growing in the United States as a result of increased patient satisfaction demands, cost containment, and quality improvement. Perinatal nurses are commonly charged with researching available computer software and hardware, making purchasing decisions, developing menus and forms, orienting users, and maintaining and upgrading systems. The decision to chart and archive by computer as well as installation and maintenance issues mandate that nurses increase their computer-related knowledge. The article reviews information related to CPR capabilities and rationales for purchase decisions, implementation and staff development issues, ergonomic and maintenance considerations, and realistic expectations of a CPR to provide perinatal nurses who are involved in purchasing, implementing, and maintaining these systems with a timely understanding of important elements that they need to know to make this effort successful. Copyright (c) 1999 by Aspen Publishers, Inc.